2007
DOI: 10.1007/s11121-006-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Similarities and Differences in the Association Between Risk and Protective Factors and Self-Reported Serious Delinquency

Abstract: Boys consistently report higher rates of serious offending during late adolescence than do girls, yet research is mixed regarding the ways in which males and females may differentially experience risk and protection in their families, schools, peer groups, and as individuals. This article examines gender differences in 22 psychosocial risk and protective factors associated with serious delinquency. Based on self-reported information from 7,829 10th-grade students completing the Communities That Care Youth Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
124
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 32 publications
14
124
2
4
Order By: Relevance
“…Sex did not significantly contribute to the classification of violent versus non-violent offense group membership, and was not retained in the stepwise model. This is inconsistent with research suggesting that being male is a risk factor for violent offending (Broidy et al, 2003;Fagan et al, 2007;Gorman-Smith & Loeber, 2005;Hart et al, 2007;Kroneman et al, 2004;Liu & Kaplan, 2004;Piquero & Sealock, 2004). This suggests that at least in this particular sample, violent and nonviolent offending was more evenly distributed among males and females than prior studies have found.…”
Section: Tablementioning
confidence: 75%
See 2 more Smart Citations
“…Sex did not significantly contribute to the classification of violent versus non-violent offense group membership, and was not retained in the stepwise model. This is inconsistent with research suggesting that being male is a risk factor for violent offending (Broidy et al, 2003;Fagan et al, 2007;Gorman-Smith & Loeber, 2005;Hart et al, 2007;Kroneman et al, 2004;Liu & Kaplan, 2004;Piquero & Sealock, 2004). This suggests that at least in this particular sample, violent and nonviolent offending was more evenly distributed among males and females than prior studies have found.…”
Section: Tablementioning
confidence: 75%
“…Research examining sex differences in risk factors for delinquent behaviors has suggested that males and females demonstrate unique developmental pathways (Broidy et al, 2003;Fagan, Van Horn, Hawkins, & Arthur, 2007;Gorman-Smith & Loeber, 2005; Hart, O'Toole, Price-Sharps, & Shaffer, 2007;Kroneman, Loeber, & Hipwell, 2004;Liu & Kaplan, 2004;Piquero & Sealock, 2004). For example, a multi-national study conducted by Fagan and colleagues (2007) examined risk factors in 7,000 adolescents and found a significant relationship between early aggressive behaviors and continuous delinquency among males only.…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents may be more likely to monitor their daughters' behavior more than their sons (Bottcher, 1995). Further, parents may be more likely to accept delinquent behavior on behalf of their sons than their daughters (Fagan, Van Horn, Hawkins, & Arthur, 2007). Females who display impulsive behavior may be monitored and supervised more closely than males (Bottcher, 1995), thereby limiting their opportunity to engage in violence.…”
Section: Discussionmentioning
confidence: 99%
“…School characteristics that encourage students' involvement and positive interactions have been consistently noted as significant protective factors (Arthur et al, 2002;O'Brien et al, 2013;Wasserman et al, 2003). Previous studies also show the complex and dynamic patterns of youth violence by students' demographics: In general, male and older youth often appear to be at-risk populations who have higher levels of risk factors and lower levels of protective factors leading to increased involvement in violence (Fagan et al, 2011;Fagan et al, 2007;Herrenkohl et al, 2000).…”
mentioning
confidence: 99%